Entrepreneurship : successfully launching new ventures - Barringer, Bruce R.; Ireland, R. Duane (Boston, Massachusetts : Pearson, 2012)
The purpose of this book is to introduce you, our readers and students of entrepreneurship, to the entrepreneurial process. We do this because evidence suggests that the likelihood entrepreneurs will be successful increases when they thoroughly understand the parts of the entrepreneurial process as wells as how to effectively use those parts.
Decision to become an entrepreneurship -- Developing successful business ideas -- Moving from an idea to an entrepreneurial firm -- Managing and growing an entrepreneurial firm
Includes bibliographical references and index.
Keywords: ENTREPRENEURSHIP